Preferensi Kecoak Amerika Periplaneta americana (L.) (Blattaria : Blattidae) terhadap Baiting Gel - Farah Ghina Arifah; Retno Hestiningsih; Rully Rahadian (Jurnal Kesehatan Masyarakat (Undip), 2016)
Cockroach Periplaneta americana is a type of species cockroach that is most abundant in an urban environment in Indonesia. Cockroaches can be a mechanical vector of various pathogens such as fungi, viruses, bacteria and protozoa. Baiting gel is one way of controlling cockroaches. Each baiting gel has a different efficacy of the species and location. This study aimed to analyze the differences in preferences Periplaneta americana against baiting commercial gel with active ingredient imidacloprid (BTX) and fipronil (MFF). Research conducted at the Laboratory of Entomology FKM Diponegoro University. The study design used is a true experiment with repeating the experiment 3 times. Data were analyzed using independent t-test (α = 0.05). Result of observation showed that in the nymph stage Periplaneta americana preference no significant difference to the baiting gel BTX and MFF with p value 0.710. So also, on the stage of imago Periplaneta americana preference no significant difference to the baiting gel BTX and MFF with p value 0,849.